Morality and boundaries in Paul - Peerbolte, Bert Jan Lietaert (HTS teologiese studies, 2012)
In the Pauline communities, ethics, ethos and identity were closely intertwined. This essay analyses the way in which Paul emphasised the mental boundaries of the Christ communities to turn them into moral boundaries. In this process, the fencing off of these communities over against their past and their present was a fundamental feature of Paul’s reasoning. The communities thus became fenced off from their past, because the Christ event was seen as causing a major change in history. This change affected both Gentile and Jewish believers. At the same time, Paul stressed the boundaries with the outside world: he characterised the inside world as the loyal remnant of Israel, consisting of Jews and Gentiles alike, and pointed out that this group is the group of the elect ‘saints’. The perspective with which Paul looked at ethics and morality inside this group was strongly coloured by the assumed identity of this group as ‘Israel’. Even though the Mosaic Law was no longer the focal point for the identity of this eschatological Israel, the ethical demands Paul mentioned over against the members of this new Israel were highly influenced by the morality of the law. For Paul, sanctification was a fundamental ideal, and this ideal reflected the spirituality of the Holiness Code of Leviticus. This particular ethical model was framed by the awareness that Paul (and Christ before him) was ‘sent’ by God, much in the same way the prophets of Israel themselves had been sent.